FACTORS INFLUENCING INFECTION, SPREAD AND SEVERITY OF TWO COLLETOTRICHUM SPECIES ON COWPEA (VIGNA UNGUICULATA (L.) WALP.) UNDER DIFFERENT CROPPING SYSTEMS (1991)
Screenhouse and field experiments were conducted between 1987and 1989to investigate the factors affecting infection, severity and spread of two diseases, anthracnose, caused by Colletotrichum lindemuthianum, and brown blotch, caused by Colletotrichum truncatum. The following factors were studied: reaction of cowpea genotypes to infection, methods and time of inoculation in screening cowpea seedlings for resistance; plant spacing, genotype and cropping pattern in mono-cowpea and cowpea-maize intercrop; and time of cowpea introduction into cowpea-maize association. Cowpea varieties IT82E-60, IT81D-1137, and Vita-7were most susceptible to anthracnose whereas TVx 3236, IT81D-994 and IT81D-975were most resistant. Varieties IT82E-60, IT82D-699 and Ife Brown were most susceptible to brown blotch whereas TVx 3236, Vita-7, and IT8ID-1137were most resistant. Wrapping of wounded seedlings with inoculum meal of Colletotrichum at 21 days after seedling emergence enhanced optimal conditions for infection and disease development with a clear distinction between susceptible and resistant varieties. Significantly lower incidence and severity of the diseases occurred on intercropped cowpea than monocrop. Though incidence values of 25 and 43% on pods from intercropped cowpea and sole cowpea infected with C. lindemuthianum were recorded, the results indicated that the sole cowpea had higher seed yield than the intercropped. Yield averages of 458and 678kg/ha were obtained from intercropped and sole cowpea with anthracnose infection. Increasing cowpea spacing, between- and within-rows, reduced the infection and severity of both Colletotrichum species on cowpea in maize and non-maize stands. Infection rates for the pathogens were lower on cowpea intercropped than on sole and infection rates increased as plant spacing decreased. Disease infection, severity and spread significantly increased with increase in age among all the tested varieties. Infection rates were highest on IT82E-16(semi-erect type) and lowest on IT84S-2246-4(erect type). Thus, the erect variety proved more suitable than the spreading type in reducing the spread of both diseases. Cropping pattern significantly affected the incidence and severity of the fungi on cowpea decreasing generally in the order Sole > Strip > Intrarow > Doublerow > Interrow. Planting cowpea one week before maize and planting both crops simultaneously reduced the incidence and severity of the two fungi on cowpea more than when it was introduced later into maize. Infection rates were lowest on cowpea planted simultaneously with maize.